The relation of feathering and overflow fat of lamb carcasses to the grade of the lamb, degree of marbling, and market value of the lamb - Mackintosh, D.L.; Merkel, R.A.; Menzies, C.S. (Kansas Agricultural Experiment Station, 2011)
This project was undertaken the spring of 1960 to attempt to determine the relationship, if any, of internal fats, overflow, and feathering to the degree of marbling in the longissimus dorsi muscle, the grade of the carcass, and the relationship of marbling to the palatability of the meat. Eighty-eight lambs were slaughtered in 1960: 120 in 1961; and about 80 will be slaughtered this spring.
Keywords: Meat; Feathering; Marbling degree; Market value